Impact of HBV genotype and mutations on HBV DNA and qHBsAg levels in patients with HBeAg‐negative chronic HBV infection. Issue 11 (10th April 2018) - Kuhnhenn, L.; Jiang, B.; Kubesch, A.; Vermehren, J.; Knop, V.; Susser, S.; Dietz, J.; Carra, G.; Finkelmeier, F.; Grammatikos, G.; Zeuzem, S.; Sarrazin, C.; et al.
Summary: Background: HBV DNA and quantitative (q)HBsAg levels as prognostic markers for HBV‐related disease are mostly validated in Asia and their significance in Western populations is uncertain. Aim: To analyse the impact of the HBV genotype and frequent mutations in precore (PC), basal core promoter (BCP) and preS on HBV DNA and qHBsAg levels. Methods: HBV DNA and qHBsAg serum levels of 465 patients with HBeAg‐negative chronic HBV infection were correlated with the HBV genotype and mutations in PC, BCP and preS. For a detailed analysis of the molecular virology, genotype A2 genomes harbouring these mutations were analysed for replication efficacy and HBsAg release in cell culture. Results: While no impact of the HBV genotype on HBV DNA levels was observed, qHBsAg levels differed up to 1.4 log among the genotypes ( P  < 0.001), reflected by large differences regarding the 1000 IU/mL HBsAg cut‐off. While PC mutations were associated with higher ( P  < 0.001), BCP mutations were associated with lower HBV DNA levels ( P  < 0.001). Higher qHBsAg levels were associated with preS and lower levels with PC mutations ( P  < 0.001 and P  = 0.001, respectively). The cell culture experiments revealed a higher HBsAg release and shorter filaments in case of a HBV genome harbouring a preS deletion. In contrast, a perinuclear HBsAg accumulation was detected for the PC and BCP‐variants, reflecting an impaired HBsAg release. Conclusions: qHBsAg serum levels depend on the HBV genotype and together with HBV DNA levels on frequent mutations in PC, BCP and preS in HBeAg‐negative patients. qHBsAg cut‐offs when used as prognostic markers require genotype‐dependent validation. Abstract : Linked Content This article is linked to Alexopoulou and Karayiannis, Kuhnhenn et al and Chen et al papers. To view these articles visithttps://doi.org/10.1111/apt.14681 ;https://doi.org/10.1111/apt.14793 ;https://doi.org/10.1111/apt.14815 andhttps://doi.org/10.1111/apt.14836 .